THE EFFECT OF A TRAINING PROGRAM ACCORDING TO CONCEPT MAPPING ON NURSING STUDENTS CRITICAL THINKING - Krongyudh, Somruk; Thoraphan, Ruangrit; Sungsakul, Wimonpan; Kasamrat, Chanikan; Saenkammuen, Rassawan; Prasanwon, Katakorn (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2022)
The objective of this research was to study the effect of concept mapping teaching and learning on critical thinking. The sample was the 2nd year nursing students, 179 in total, who studied pediatric nursing at Boromarajonani College of Nursing Sappasitthiprasong. The research tools were concept mapping lesson plan, a critical thinking skill assessment form, and a critical thinking abilities assessment form. The Cronbach's alpha coefficients was .87 and KR-20 was .72, respectively. The data were analyzed by descriptive statistics, mean, and standard deviation. The results showed that the writing of concept mapping in child and adolescent nursing curricula made nursing students' critical thinking skills and abilities better than before. Therefore, it should be encouraged to use concept mapping teaching and learning for nursing students in other subjects of nursing courses.